THE IMPACT OF A DISAGGREGATION STRATEGY WITH SUPPLEMENTARY DISPLAYS TOWARDS BALANCED SCORECARD PERFORMANCE EVALUATION - Frisky Jeremy Kasingku; Goedono . (Journal of Indonesian Economy and Business (JIEB), 2017)
Balanced Scorecard has become a popular management tool around the world. Despite its benefits, the balanced scorecard creates a bias called the common- measures bias. The bias associated with a balanced scorecard should be eliminated so that the optimal benefits of the balanced scorecard can be obtained. To eliminate the bias, a disaggregation strategy is suggested. This disaggregation strategy is found to be a mitigation strategy to solve the common-measures bias. However, there is a small amount of empirical evidence about the quality of the decisions produced by using a disaggregation strategy. Furthermore, to increase the decisions’ quality, an information display was found to be helpful. Therefore, this study aimed to investigate the effect of a disaggregation strategy, in the context of a balanced scorecard, toward the decisions’ quality regarding the balanced scorecard’s performance evaluation with a different information display. This study used an experimental method with the design of 3x2x2 between the subject’s factorial designs. The results indicated that decision makers with supplementary tabular and graphic displays would exhibit a greater judgment consensus than decision makers who were given traditional separate displays. Moreover, those who received the supplementary table displays exhibit a greater judgment consensus and consistency than those who were given a graphical display. In conclusion, a disaggregation strategy with table and graphic displays could improve a judgment’s consensus, a traditional display can improve a judgment’s consistency, and a table display could exhibit greater judgmental consensus and consistency than a graphic display. This study contributed theoretically and practically.